Efficacy of supplemental MCT oil on seizure reduction of adult drug-resistant epilepsy - a single-center open-label pilot study - Rasmussen, Emmaline; Patel, Vimal; Tideman, Samuel; Frech, Robert; Frigerio, Roberta; Narayanan, Jaishree (Nutritional neuroscience, 2023)
We set out to determine whether adding medium chain triglyceride (MCT) oil as a dietary supplement to standard diet in adult subjects with intractable epilepsy in a U.S. neurology clinical practice was associated with a reduction in number of seizures. We secondarily aimed to determine whether subjects experienced any side effects and whether there was a presence of urinary ketones while using MCT oil as a dietary supplement. Adult patients with intractable epilepsy were recruited at standard of care clinical visits with their epileptologist. Once enrolled, subjects were instructed to supplement their diet with MCT oil as tolerated twice daily for three months (including a 1-2 week titration period, followed by a 1-2 week tapering off window) while keeping a seizure diary to record total number of seizures, presence of urinary ketones, and any side effects. Our data although limited by small sample size, shows that there is an estimated 42% reduction (p < 0.0001) in the rate of seizures. The MCT oil supplementation was well tolerated by most subjects except for minor GI side effects like nausea and loose stools. Most subjects developed ketones in their urine at some point during the trial. MCT oil supplementation reduced seizure frequency in study participants. The reported side effects included mild nausea, stomachache, loose stools. A placebo-controlled study will be more informative.